DETERMINANTS OF HEDGING DECISIONS WITH DERIVATIVE INSTRUMENTS IN FOREIGN EXCHANGE BANKS LISTED ON THE INDONESIA STOCK EXCHANGE - Winda Rika Lestari; Bella Noviani Pratiwi (SEAN Institute, 2023)
Hedging is an action a company can take to minimize the exchange rate risk it faces. Hedging will be useful for achieving financial and macroeconomic stability with good management of corporations that can make financial markets more developed and healthy. But there are still companies that do not hedge because they do not know exactly the factors that influence hedging decisions. This study aims to empirically examine the effect of firm size, debt levels, liquidity, and cash flow volatility on hedging decisions at foreign exchange banks listed on the IDX. This study used a purposive sampling method so as to get a sample of 23 companies. The statistical method uses logistic regression analysis, by testing the hypothesis of the Wald statistical test. The results of this study indicate that liquidity has a significant negative effect on hedging decisions. Meanwhile, company size, debt level, and flow volatility have no effect on hedging decisions.